Effect of differently coated silver nanoparticles on hemostasis. (4th July 2021) - Milić, Marija; Vuković, Barbara; Barbir, Rinea; Pem, Barbara; Milić, Mirta; Šerić, Vatroslav; Frőhlich, Eleonore; Vinković Vrček, Ivana
Abstract: With the emergence of nano-enabled medical devices (MDs) for the use in human medicine, ensuring their safety becomes of crucial importance. Hemocompatibility is one of the major criteria for approval of all MDs in contact with blood (e.g. vascular grafts, stents, or valves). Silver nanoparticles (AgNPs) are among the most used nanomaterials for MDs due to their biocidal activity; however, detailed knowledge on their hemostatic effects is still lacking. This study aimed to evaluate comprehensively AgNPs effects on hemostasis in human blood by exploiting combination of affordable and clinically relevant techniques. Differently stabilized AgNPs were prepared using sodium bis(2-ethylhexyl)sulphosuccinate (AOT), polyvinylpyrrolidone (PVP), poly-L-lysine (PLL), and bovine serum albumin (BSA) as coating agents. They were tested for hemolytic activity, induction of platelet aggregation, plasmatic coagulation, thrombin generation, and hemostasis in whole blood. All AgNPs were found to cause dose-dependent hemolysis. The BSA-, AOT-, and PVP-coated AgNPs delayed plasmatic coagulation, while only PLL-AgNPs inhibited plasmatic coagulation, induced platelet activation, and interfered with hemostasis by delaying clotting time and decreasing clot firmness in whole blood. Obtained results demonstrate that a combination of different techniques should be used for reliable assessment of AgNPs hemostatic effects highlighting the need for a standardized approach in sampling and experimental protocols.